The translation of metaphors related to beauty in two English versions of Hong Lou Meng / Wang Hui - Wang , Hui (2019)
Hong Lou Meng (abbreviated as HLM) is a novel written by Cao Xueqin (1715-1763) in Qing dynasty. As one of four of the most famous and greatest novels in China, HLM enjoyed high reputation in the history of Chinese literature. In HLM, the description of appearance of young women characters is anything but prevalent; Cao used rhetoric devices of metaphors and similes to present abstract beauty into something visual. However, it is not an easy task to deliver the beauty related concepts into another language, as English and Chinese literatures do not share the same standards of beauty and the choice of images; instead the translation of metaphors is influenced by differences between them. For example, if the image in the source text (abbreviated as ST) is kept in the target text (TT), it is difficult for the target language (TL) readers to understand if they do not have the knowledge of the source language (SL) culture; at the same time, if the image is in ST is abandoned in the TT, the beauty of it is lost. To investigate the translation of “women’s beauty”, this paper concentrated on translation of metaphor utilized in describing the beauty of all females, into English by David Hawkes and John Minford (1986) (abbreviated as DH) and Yang Xianyi and Gladys Yang (1978) (abbreviated as YY). Adopting the theoretical framework of domesticating and foreignization proposed by Venuti (1995) and Cui (2012), this study aimed at explaining ways the two selected English versions of HLM translated the abstract image of women’s beauty. After examining the translation of metaphors related to “feminine beauty”, the result confirmed that DH and YY were likely to employ foreignization in translation, respectively at 55.9% and 64.9%. At the same time, both YY and DH applied a good combination of domestication at 34.2% and 43.2%, respectively. Through this study, neither foreignization nor domestication was applied on shared metaphors, in this case, the researchers employed "neutral" as a new category. Yang and David Hawkes employed neutral at merely 0.9%. Furthermore, in the translation of the three metaphor types: dominant metaphor, recessive metaphor and compound metaphor in both versions of novel, the translators were likely to adopt strategy of foreignization in translating dominant metaphors, compared with the other two types of metaphors, as there were connective words in dominant metaphor, thus, they paid more attention to the cultural aspect as well as have a tendency to retain the image of ST to TT. In addition, it was found that YY and DH tended to utilize similar strategies in translating metaphors related to beauty, accounted for up to 73%; conversely, 27% was a percentage representing YY and DH employing different translation strategies.